Comparative Analysis between Singular Spectral Analysis and Empirical Mode Decomposition for Structural Damage Detection - Elisa C. González; Gladys E. Salcedo; Leonardo Cano (Ingeniería, 2023)
Context: In recent years, thanks to technological advances in instrumentation and digital signal processing, noninvasive methods to detect structural damage have become increasingly important. Vibration-based structural health monitoring (SHM) techniques allow detecting the presence and location of damage from permanent changes in the fundamental frequencies of signals. A successfully employed method for damage detection is empirical mode decomposition (EMD). Another method, less used in this field of study, is singular spectral analysis (SSA). This paper describes both methods and presents a simulation study aimed at comparing them and identifying which one is more effective in detecting structural damage.